Informe macro financiero del departamento del Quindío vigencia 2013 (2014)
This essay shows the process of realization of the macro financial report of the department of Quindío, period of validy is the year 2013, it supports the information by sector (municipalities, decentralized bodies, office of the governor and hospitals), it analyzes the tendencies and results of the financial accounting situation, Budget and management of the control subjects that belong to the department of Quindío, conforming the information exposed by these in the application consolidated of finance ministry and public interest (CHIP), resiewing the veracity, behavior, transparency and the consistence in the balance sheet, income statement, execution of income and expenses, programme of income and expenses, ]Allowing the evaluation of the management that is being made by every single of these entities, noting if they are honoring their obligation and is responsibilities disposed by law. The macro financial report once clarified and verified the information, it allows announcing a concept about the financial, Budget and management situations of the department of Quindío during the year of 2013, and in the same way informing about the control subjects so they can improve their administration, allowing a positive improvement to the department of Quindío in general